Outcome Comparison of Endovascular and Open Surgery for the Treatment of Acute Superior Mesenteric Artery Embolism: A Retrospective Study - Li, Wenrui; Cao, Saisai; Zhang, Zhiwen; Zhu, Renming; Chen, Xueming; Liu, Bin; Feng, Hai (Frontiers in Surgery, 2022)
Background Few centers have adopted endovascular revascularization for the treatment of superior mesenteric artery embolism (SMAE). We sought to evaluate the efficacy of endovascular therapy for the treatment of SMAE and identify post-treatment prognostic factors. Methods The clinical data of 41 patients with acute SMA embolism between 2013 and 2021 were retrospectively reviewed. Patients with mesenteric artery thrombosis, mesenteric venous thrombosis, and who had only conservative treatment were excluded. Results Forty-one consecutive patients were identified with SMAE (median age, [range] 35–86 years). Endovascular therapy was initiated in 14 patients with no clinical evidence of bowel necrosis, with mainly mechanical thrombectomy, and technical success was achieved in 93%. Endovascular therapy had advantages in duration surgery time, blood loss, bowel rest time, ICU time, and ventilator use. There was no difference in bowel necrosis, length of necrotic bowel resected, or in-hospital mortality between the two groups. An initial white blood cell (WBC) count >15 × 103/dl and neutrophil count >13 × 103/dl were associated with an increased risk of bowel necrosis, and an initial WBC count, renal function, American Society of Anesthesiologists (ASA >3) and necrotic bowel >2 m were associated with increased mortality. Conclusions Endovascular treatment has altered the management of SMAE, and it may be adopted in selected patients who are not at risk for bowel necrosis. Avoidance of bowel necrosis patients and close monitoring for bowel necrosis are important.